Karst structure filling grouting material

CN123003232APending Publication Date: 2026-10-30中国水利水电第七工程局有限公司 +1
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202611069621.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-07-17
Publication Date
2026-10-30

AI Technical Summary

Technical Problem

[0012]针对上述现有技术的不足,本发明提供一种环保低碳的岩溶结构充填注浆材料及其制备方法,旨在解决现有注浆材料在富水动水环境中触变性不足、抗冲刷能力差、增稠与流动性矛盾突出、硬化结石体力学性能劣化的问题

Benefits of technology

[0029]与现有技术相比,本发明提供的岩溶结构充填注浆材料及其制备方法具有以下显著的有益效果:

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN123003232A_ABST
    Figure CN123003232A_ABST
Patent Text Reader

Abstract

The application discloses a karst structure filling grouting material, and belongs to the technical field of concrete. The karst structure filling grouting material provided by the application contains, by weight, 50-60 parts of ordinary Portland cement, 15-25 parts of sulphoaluminate cement, 10-20 parts of fly ash, 3-8 parts of silica ash, 0.5-2 parts of a thixotropic agent, 1.0-1.5 parts of a polycarboxylate water reducing agent, 0.1-0.3 parts of hydroxypropyl methyl cellulose, 0.5-1.0 parts of sodium metaaluminate, 0.03-0.08 parts of sodium gluconate and 50-60 parts of water. The thixotropic agent is modified bentonite obtained by organic intercalation and surface covalent graft modification of sodium-based bentonite by using a silane-polyether-quaternary ammonium salt modifier. The grouting material has excellent thixotropic recovery, dynamic water scouring resistance, controllable setting time, high compressive strength and high impermeability grade, and is suitable for structure filling grouting under dynamic water conditions in karst areas.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of concrete technology, specifically to a grouting material for filling karst structures. Background Technology

[0002] High permeability control and low-carbon construction in karst formations have become the dual goals of green development in underground engineering. Karst refers to the comprehensive geological processes and phenomena resulting from the chemical dissolution of soluble rocks by water. Karst areas account for approximately one-third of my country's land area, and numerous underground engineering projects traverse these regions. In karst formations, water-rich fissures, caves, and conduits often exhibit characteristics of large water volume, high flow velocity, and abundant recharge. Grouting is one of the most effective means of treating adverse karst geological formations and sealing groundwater channels. The performance of the grouting material directly determines the effectiveness of the grouting. Therefore, developing grouting materials suitable for water-rich karst environments, possessing excellent fluidity, erosion resistance, controllable setting, and high strength and impermeability, is a key technological requirement for the safe construction of underground engineering projects in karst areas.

[0003] Currently, the grouting materials commonly used in karst filling grouting projects mainly include the following categories: (I) Ordinary cement-based grouting materials: These materials use ordinary Portland cement as the main cementing material and have advantages such as high strength, good durability, and low cost, making them the most widely used grouting materials currently. However, ordinary cement grout does not have thixotropic properties, and in water-rich and flowing water environments, the grout is easily diluted and dispersed by groundwater, resulting in a low retention rate, a bleeding rate that is usually as high as 8% to 15%, and a stone formation rate of less than 90%.

[0004] (II) Cement-Bentonite Grouting Materials: Bentonite is incorporated into cement-based materials to improve grout stability through its water absorption and expansion properties. For example, CN108585692A discloses a grouting material suitable for filling karst caves, composed of cement, fly ash, and bentonite. However, in the high ionic strength environment of cement grout, ordinary sodium-based bentonite exhibits interlayer Na... + Ca, which is easily released during cement hydration 2+Displacement leads to surface-to-surface aggregation (flocculation) of the lamellae, forming an uneven flocculated structure that causes the slurry to exhibit a pseudo-thickness phenomenon—although the apparent viscosity is high, the effective dispersion is poor, and the fluidity is severely reduced. Simultaneously, the flocs trap a large amount of free water, which is released upon shearing, resulting in a persistently high bleeding rate. More importantly, ordinary bentonite relies solely on interlayer hydration and expansion to provide a thickening effect and lacks the thixotropic properties of shear thinning and resting recovery, making it unable to quickly rebuild structural strength under dynamic water erosion conditions. Furthermore, although traditional organically modified bentonite (such as hexadecyltrimethylammonium bromide intercalated bentonite) introduces hydrophobic long chains through ion exchange to improve interlayer swelling, it lacks effective steric hindrance dispersing groups, resulting in limited peeling and dispersion of the sheets in cement slurry and difficulty in forming a uniform three-dimensional network. Moreover, its long-chain alkyl groups and the side chains of polycarboxylate superplasticizer (PCE) have steric hindrance competition and hydrophobic interactions on the surface of cement particles, leading to a decrease in PCE dispersion efficiency and deterioration of slurry dispersibility, making it difficult to achieve a balance between high fluidity and high thixotropy at low water-cement ratios.

[0005] (III) Cellulose Ether Thickening Grouting Materials: Water-soluble cellulose ethers such as hydroxypropyl methylcellulose (HPMC) are added to cement grout to improve the viscosity and water retention of the grout through molecular chain hydration. However, the mechanism of action of cellulose ethers is physical entanglement and hydration thickening of linear molecular chains, rather than the formation of a reversible three-dimensional network structure; therefore, the grout does not possess thixotropic recovery capability. Under dynamic water scouring conditions, cellulose ether-thickened grout exhibits a viscous but not tough state, with limited scouring resistance. Furthermore, HPMC molecular chains, through hydrogen bonds and Ca... 2+ Complexation adsorbs onto the surface of cement particles, forming a thick hydration adsorption layer, which delays C3S hydration and CSH crystal growth, adversely affecting both early and later strength.

[0006] (iv) Chemical grouting materials: Polyurethane, epoxy resin and other chemical grouting materials have the advantages of rapid curing and good bonding performance, but they are expensive, have complicated construction processes, and some materials pose environmental risks, making them unsuitable for large-scale karst filling projects.

[0007] Based on the above analysis, the existing water-rich karst grouting materials mainly face the following core unresolved technical challenges: First, thixotropy is lacking. Existing thickeners, such as ordinary sodium bentonite and cellulose ethers, rely solely on interlayer hydration and expansion or physical entanglement of molecular chains for their mechanism of action, lacking the reversible thixotropic properties of shear thinning and resting recovery. Therefore, after the viscosity of the slurry decreases during pumping shearing, it cannot quickly rebuild its structural strength in a short time after being injected into a dynamic water environment, resulting in severely insufficient erosion resistance and significant slurry loss.

[0008] Second, dispersibility deterioration. In the high ionic strength environment of cement slurry, ordinary sodium-based bentonite's interlayer cations are easily converted by Ca...2+ Displacement leads to surface-to-surface aggregation, forming an uneven flocculated structure, resulting in false thickening and persistently high bleeding rates. While traditional organically modified bentonite (such as hexadecyltrimethylammonium bromide intercalated bentonite) improves interlayer hydrophobicity to some extent, it lacks effective steric hindrance dispersing groups, has limited delamination, and struggles to achieve high flowability at low water-cement ratios.

[0009] Third, the contradiction between thickening and fluidity is prominent. In existing technologies, improving the scour resistance of slurry usually relies on increasing the amount of bentonite or cellulose ether, but this significantly reduces the fluidity of the slurry and may even cause a loss of pumpability. The root cause is the lack of synergistic design between existing thickening mechanisms (flocculation or hydration thickening) and dispersion mechanisms (water-reducing agents). There is a compatibility conflict between thickening components and dispersion components in cement slurry, making it difficult to meet the dual requirements of high fluidity and high scour resistance.

[0010] Fourth, the performance of the karst mass deteriorates. Due to the insufficient flocculation and agglomeration of ordinary bentonite and the lack of uniformity of cellulose ether, local defects and interconnected pores are easily introduced into the interior of the hardened karst mass, resulting in high water bleeding rate, low karst mass, and decreased compressive strength and impermeability grade, making it difficult to meet the durability requirements for long-term stable filling of karst structures.

[0011] Therefore, it is evident that, while maintaining the good fluidity and pumpability of the grout, it is crucial to endow it with thixotropic properties that enable rapid reconstruction of structural strength in a dynamic water environment, while simultaneously ensuring the high strength and high impermeability of the hardened rock mass. This is a technical bottleneck that urgently needs to be overcome in the field of water-rich karst grouting materials. Summary of the Invention

[0012] To address the shortcomings of the existing technologies, this invention provides an environmentally friendly and low-carbon karst structure filling grouting material and its preparation method, aiming to solve the problems of insufficient thixotropy, poor erosion resistance, prominent contradiction between thickening and fluidity, and deterioration of mechanical properties of hardened stone bodies in existing grouting materials in water-rich and dynamic water environments.

[0013] The technical solution for achieving the objective of this invention is as follows: A grouting material for filling karst structures, by weight, comprises: 50-60 parts of ordinary silicate cement; 15-25 parts of sulfoaluminate cement; 10-20 parts of fly ash; 3-8 parts of silica fume; 0.5-2 parts of thixotropic agent; 1.0-1.5 parts of polycarboxylate superplasticizer; 0.1-0.3 parts of hydroxypropyl methylcellulose; 0.5-1.0 parts of sodium aluminate; 0.03-0.08 parts of sodium gluconate; and 50-60 parts of water; wherein the thixotropic agent is modified bentonite obtained by organic intercalation and surface covalent grafting modification of sodium-based bentonite using a silane-polyether-quaternary ammonium salt modifier.

[0014] In a specific embodiment, the silane-polyether-quaternary ammonium salt modifier is prepared by the following steps: (1) reacting a polyamine with an isocyanate-based silane to introduce silane groups and urea groups to obtain a urea polyamine containing silane groups; (2) reacting the urea polyamine containing silane groups with a polyether carboxylic acid active ester to introduce a polyether chain to obtain a polyether-amide-urea-silane intermediate; (3) subjecting the polyether-amide-urea-silane intermediate to a haloalkane alkylation and quaternization reaction with a quaternizing agent to introduce quaternary ammonium salt groups to obtain the silane-polyether-quaternary ammonium salt modifier.

[0015] In one specific embodiment, the polyamine is diethylenetriamine, the isocyanate-based silane is 3-isocyanate-based propyltrimethoxysilane, and the molar ratio of the polyamine to the isocyanate-based silane is (5~15):1.

[0016] In one specific embodiment, the polyether carboxylic acid is methoxy polyethylene glycol-carboxylic acid with an average molecular weight of 500-600.

[0017] In one specific embodiment, in step (3), the haloalkane is a bromoalkane with 6 to 12 carbon atoms, and the quaternizing agent is iodomethane or dimethyl sulfate.

[0018] In one specific embodiment, the modified bentonite is prepared by the following steps: (1) Disperse sodium-based bentonite in water, add silane-polyether-quaternary ammonium salt modifier to carry out intercalation reaction, and obtain intercalated bentonite; (2) The intercalated bentonite is subjected to a hydrothermal reaction under alkaline conditions, so that the silane groups in the modifier are hydrolyzed and condensed with the hydroxyl groups on the surface and edge of the bentonite sheets to obtain modified bentonite.

[0019] In a specific embodiment, in step (1), sodium-based bentonite is dispersed in deionized water at a solid-liquid ratio of 1:(15~25), the amount of silane-polyether-quaternary ammonium salt modifier added is 2wt%~5wt% of the bentonite mass, the reaction temperature is 30~45℃, and the reaction time is 1~3h; in step (2), the pH is adjusted to 9~11, the reaction temperature is 50~70℃, and the reaction time is 2~4h; the cation exchange capacity of the sodium-based bentonite is 95~110mmol / 100g, and the montmorillonite content is ≥75%.

[0020] This invention also protects a method for preparing grouting materials for filling karst structures, comprising the following steps: S1. Disperse the thixotropic agent in a portion of water to prepare a thixotropic agent stock solution; S2. Dry mix ordinary Portland cement, sulfoaluminate cement, fly ash, and silica fume evenly; S3. Add the remaining water and the thixotropic agent mother liquor described in S1, and stir to obtain a slurry; then add the polycarboxylate superplasticizer solution and hydroxypropyl methylcellulose solution, and continue stirring; S4. Finally, add the mixed solution of sodium aluminate and sodium gluconate, stir evenly, and immediately carry out the grouting operation.

[0021] In a specific embodiment, in S1, the modified bentonite is added to water accounting for 30% to 50% of the total water volume, and stirred at a high speed of 1000 to 2000 rpm for 5 to 15 minutes, and then allowed to stand to defoam; in S2, the dry mixing time is 1 to 3 minutes; in S3, the mixture is first stirred at a low speed for 1 to 3 minutes, and then the polycarboxylate superplasticizer solution and hydroxypropyl methylcellulose solution are added and stirred at a medium speed for 1 to 3 minutes; in S4, the mixture is stirred at a low speed for 0.5 to 2 minutes; from the addition of the setting agent to the completion of grouting, the operating window is controlled within 30 to 45 minutes.

[0022] The present invention also protects a silane-polyether-quaternary ammonium salt modifier, which is prepared by the following steps: (1) reacting a polyamine with an isocyanate-based silane to obtain a urea polyamine containing a silane group; (2) reacting the urea polyamine containing a silane group with a polyether carboxylic acid active ester to obtain a polyether-amide-urea-silane intermediate; (3) subjecting the polyether-amide-urea-silane intermediate to a haloalkane alkylation and quaternization reaction with a quaternizing agent to obtain a silane-polyether-quaternary ammonium salt modifier.

[0023] In one specific embodiment, the polyamine is diethylenetriamine, the isocyanate-based silane is 3-isocyanate-based propyltrimethoxysilane, and the molar ratio of the polyamine to the isocyanate-based silane is (5~15):1.

[0024] In one specific embodiment, the polyether carboxylic acid is methoxy polyethylene glycol-carboxylic acid with an average molecular weight of 500-600.

[0025] In one specific embodiment, in step (3), the haloalkane is a bromoalkane with 6 to 12 carbon atoms, and the quaternizing agent is iodomethane or dimethyl sulfate.

[0026] This invention also protects a modified bentonite, which is prepared by the following steps: (1) Disperse sodium-based bentonite in water, add silane-polyether-quaternary ammonium salt modifier to carry out intercalation reaction, and obtain intercalated bentonite; (2) The intercalated bentonite is subjected to a hydrothermal reaction under alkaline conditions, so that the silane groups in the modifier are hydrolyzed and condensed with the hydroxyl groups on the surface and edge of the bentonite sheets to obtain modified bentonite.

[0027] In a specific embodiment, in step (1), sodium-based bentonite is dispersed in deionized water at a solid-liquid ratio of 1:(15~25), the amount of silane-polyether-quaternary ammonium salt modifier added is 2wt%~5wt% of the bentonite mass, the reaction temperature is 30~45℃, and the reaction time is 1~3h; in step (2), the pH is adjusted to 9~11, the reaction temperature is 50~70℃, and the reaction time is 2~4h; the cation exchange capacity of the sodium-based bentonite is 95~110mmol / 100g, and the montmorillonite content is ≥75%.

[0028] Beneficial effects

[0029] Compared with the prior art, the karst structure filling grouting material and its preparation method provided by the present invention have the following significant advantages: (1) This invention uses silane-polyether-quaternary ammonium salt triple-modified bentonite as a thixotropic agent. Its silane groups form stable chemical bonds with the active hydroxyl groups on the surface and edges of the bentonite sheets through condensation reaction, which significantly improves the durability of the modified layer. The polyether chain provides strong steric hindrance, which enables the sheets to be fully peeled and dispersed in the cement slurry. The quaternary ammonium salt cation imparts electrostatic repulsion and hydrophobic association ability. The three work together to enable the bentonite sheets to construct a dense and reversible three-dimensional thixotropic network under low shear conditions, giving the slurry the characteristics of shear thinning and rapid recovery after standing. This characteristic enables the slurry to maintain low viscosity and high fluidity when pumped, and can recover structural strength in a short time after being injected into karst fissures, effectively resisting groundwater erosion and achieving the grouting goal of being able to be injected and stand firm.

[0030] (2) The polyether chains on the surface of modified bentonite and the side chains of polycarboxylate superplasticizer have good spatial compatibility and can synergistically exert a dispersing effect. This invention achieves high fluidity under low water-cement ratio conditions through the synergy of modified bentonite and polycarboxylate superplasticizer, successfully solving the technical contradiction that thickening inevitably reduces fluidity in traditional grouting materials.

[0031] (3) This invention uses a composite system of ordinary silicate cement and sulfoaluminate cement. Through the synergistic regulation of the setting-promoting effect of sodium aluminate and the retarding effect of sodium gluconate, the setting time of the grout is adapted to the needs of on-site construction. The operation window from the addition of the setting regulator to the completion of grouting is controlled within 30 to 45 minutes, which ensures the full diffusion of the grout in complex karst fissures and avoids insufficient groutability caused by excessively rapid setting.

[0032] (4) Modified bentonite is uniformly dispersed in cement paste without forming flocs, thus avoiding the introduction of local defects and interconnected pores inside the hardened body. Furthermore, the physical barrier effect of modified bentonite layers contributes more to impermeability than to its negative impact on strength—although the increase in layer network density has a slight negative impact on strength, the decrease in microscopic pore connectivity improves impermeability, demonstrating that impermeability is more sensitive to the amount of thixotropic agent than strength.

[0033] (5) The three-dimensional network structure of modified bentonite has a physical binding effect on free water, while hydroxypropyl methylcellulose assists in water retention through molecular chain hydration. The two work together to significantly reduce the bleeding rate of the slurry. The low bleeding rate ensures the volume stability of the slurry during the hardening process, reduces the generation of shrinkage cracks, and improves the bonding strength between the slurry and the karst wall.

[0034] (6) The main raw materials used in this invention are all commercially available industrial-grade products. The preparation conditions of modified bentonite are mild and easy to industrialize. The incorporation of fly ash and silica fume reduces cement usage and material costs while optimizing the microstructure of the hardened body through the pozzolanic effect. The dual-cement system composed of ordinary silicate cement and sulfoaluminate cement takes into account both the later strength stability and early setting anchoring requirements. The materials of this invention are particularly suitable for underground engineering projects in karst areas, such as tunnels, roadbeds, and dam foundations, that require large-scale filling and grouting. Attached Figure Description

[0035] Figure 1 Infrared spectra of sodium-based bentonite, silane-polyether-quaternary ammonium salt modifier, and modified bentonite 1. Detailed Implementation

[0036] The technical solutions of the present invention will be clearly and completely described below with reference to the embodiments of the present invention. Obviously, the described embodiments are only some embodiments of the present invention, and not all embodiments. Based on the embodiments of the present invention, all other embodiments obtained by those of ordinary skill in the art without creative effort are within the scope of protection of the present invention.

[0037] Unless otherwise specified, the experimental methods used in the embodiments are conventional methods, and the materials and reagents used are commercially available unless otherwise specified.

[0038] The raw materials used in the examples and comparative examples are described below: Cement 1: Ordinary Portland cement, PO 42.5R, Conch Cement; Cement 2: Sulfoaluminate cement, R·SAC 42.5, Zhengzhou Xinmi Melting Material Co., Ltd.; Fly ash: Class F, Grade II; Silica fume: SiO2 ≥ 90%; The polycarboxylate superplasticizer was purchased from Jiangsu Subote New Materials Co., Ltd., and its model is PCA®-Ⅰ high-efficiency superplasticizer. Hydroxypropyl methylcellulose: viscosity 100,000 mPa·s, Nanjing Dulai Biotechnology Co., Ltd.; Sodium aluminate: Industrial grade; Sodium gluconate: Industrial grade; Water: tap water; Silane-polyether-quaternary ammonium salt modifier: All reaction steps involving isocyanate silanes, active hydrogen amines, and NHS active esters were carried out under strictly anhydrous conditions. Glassware was dried in a 250°C oven for 2 hours and then assembled while still hot. Solvents were pretreated with molecular sieves or calcium hydride, and the moisture content was controlled to ≤100ppm.

[0039] (1) Under nitrogen protection, 0.2 mol of diethylenetriamine, which had been dehydrated by vacuum distillation, was dissolved in 150 ml of anhydrous tetrahydrofuran and cooled to -20 °C. While stirring, 0.02 mol of 3-isocyanatopropyltrimethoxysilane was slowly added dropwise to the above solution at a rate of 1 drop per second, controlling the temperature of the reaction solution to not exceed -10 °C during the addition process. After the addition was complete, stirring was continued at -10 °C for 1 h, followed by a reaction at 0 °C for 2 h. After the reaction was completed, the reaction solution was placed in a rotary evaporator and concentrated under reduced pressure at 35 °C and -0.09 MPa to remove most of the tetrahydrofuran. The residue was transferred to a short-path distillation apparatus and subjected to short-path distillation under a high vacuum of ≤0.1 mbar, a bath temperature of 100 °C, and a distillation head temperature of 80 °C to collect and recover the excess diethylenetriamine distilled off. The distillation residue was a pale yellow, transparent, viscous liquid, yielding a urea polyamine containing silane groups in 72.5% (based on 3-isocyanate-propyltrimethoxysilane).

[0040] (2) Under nitrogen protection, 0.02 mol of methoxy polyethylene glycol-carboxylic acid (mPEG-COOH, average molecular weight 550) and 0.02 mol of N-hydroxysuccinimide were dissolved in 100 ml of anhydrous dichloromethane and cooled to 0 °C in an ice bath. 0.02 mol of N,N'-dicyclohexylcarbodiimide was added, and the mixture was stirred at 0 °C for 30 min. The ice bath was then removed, and the mixture was allowed to react at room temperature for 4 h to generate an mPEG-550-NHS active ester solution. The precipitated N,N'-dicyclohexylurea was removed by filtration, and the filtrate was used directly in the next step.

[0041] 0.02 mol of the silane-containing urea polyamine obtained in step (1) was dissolved in 30 mL of anhydrous dichloromethane, and the filtrate of mPEG-550-NHS active ester was added. The mixture was cooled to 0 °C in an ice bath and stirred for 6 h. After the reaction was completed, trace amounts of insoluble matter were removed by filtration. The filtrate was dried with anhydrous sodium sulfate, filtered, and concentrated under reduced pressure at -0.09 MPa at 40 °C to obtain the crude product. The crude product was dissolved in a small amount of anhydrous dichloromethane and purified by 200-mesh neutral alumina short column chromatography. The product was eluted with a gradient of dichloromethane / methanol mixed solution at a volume ratio of 8:1. The main fraction was collected and concentrated under reduced pressure at -0.09 MPa at 40 °C to obtain a pale yellow viscous substance, namely the polyether-amide-urea-silane intermediate, with a yield of 78.5%.

[0042] (3) Dissolve 0.02 mol of the polyether-amide-urea-silane intermediate obtained in step (2) in 100 ml of anhydrous acetonitrile, add 0.04 mol of anhydrous potassium carbonate, 0.002 mol of potassium iodide and 0.024 mol of 1-bromooctane, heat to 82 °C and reflux, and stir for 14 h under nitrogen protection. After the reaction is complete, cool to room temperature, filter to remove inorganic salts, concentrate the filtrate under reduced pressure at 50 °C and -0.09 MPa to remove acetonitrile, add the residue to 60 ml of anhydrous diethyl ether, stir for 10 min, precipitate a pale yellow solid, filter, wash twice with 20 ml of anhydrous diethyl ether, and dry under vacuum at 30 °C for 6 h to obtain the tertiary amine intermediate with a yield of 88.8%.

[0043] (4) Dissolve 0.02 mol of the tertiary amine intermediate obtained in step (3) in 50 ml of anhydrous acetonitrile and add 0.06 mol of iodomethane. Under nitrogen protection, stir at room temperature for 30 h, and take samples every 8 h for TLC monitoring (neutral alumina thin-layer plate, developing solvent: dichloromethane / methanol = 5:1, iodine staining) until the starting material spot disappears. After the reaction is completed, concentrate under reduced pressure to remove acetonitrile and excess iodomethane. Dissolve the residue in 20 ml of dichloromethane / methanol at a volume ratio of 10:1 and purify by 200 mesh neutral alumina column chromatography. Elute with a dichloromethane / methanol gradient at a volume ratio of 20:1 and collect the main fraction with an Rf value of about 0.25 (neutral alumina plate, iodine staining). Concentrate under reduced pressure. Add the concentrate to 80 ml of anhydrous diethyl ether and stir vigorously to precipitate a white to pale yellow solid. The filter cake was filtered, washed with 20 ml of anhydrous diethyl ether, and dried under vacuum at 30 °C for 12 h to obtain a silane-polyether-quaternary ammonium salt modifier with a yield of 85.2%.

[0044] Sodium-based bentonite (Na-Bent): Montmorillonite content ≥75%, cation exchange capacity (CEC) 105 mmol / 100g, residue ≤5% on a 200-mesh sieve, dried to constant weight at 105℃ before use. Modified bentonite 1: (1) Disperse sodium-based bentonite in deionized water at a solid-liquid ratio of 1:20 and sonicate for 20 min. Adjust the pH to 6.0-7.0 with 1 mol / L dilute hydrochloric acid. Dissolve the silane-polyether-quaternary ammonium salt modifier in anhydrous ethanol, wherein the amount of silane-polyether-quaternary ammonium salt modifier added is 3.0 wt% of the bentonite mass, and the amount of anhydrous ethanol is 5 times the mass of the silane-polyether-quaternary ammonium salt modifier. Stir until completely dissolved. Under nitrogen protection, slowly add the ethanol solution of silane-polyether-quaternary ammonium salt modifier to the bentonite dispersion at a rate of 1-2 drops per second, controlling the system temperature not to exceed 35℃ during the addition process. After the addition is complete, raise the temperature to 40-45℃ and continue stirring for 2 h. After the reaction is complete, filter and wash with deionized water until the filtrate is free of I. -AgNO3 was detected, and intercalated bentonite filter cake was obtained.

[0045] (2) The intercalated bentonite filter cake obtained in step (1) is redispersed in deionized water (solid-liquid ratio 1:15), and the pH is adjusted to 10.0~10.5 with 10% NaOH solution. The temperature is raised to 60℃, and the reaction is stirred for 3h under nitrogen protection to allow the trimethoxysilane group in the silane-polyether-quaternary ammonium salt modifier to be fully hydrolyzed and condensed with Al-OH / Si-OH on the surface and edge of the bentonite sheets to form stable Si-O-Al / Si-O-Si covalent grafts. After the reaction is completed, the mixture is filtered, washed with deionized water until the filtrate is neutral, dried under vacuum at 80℃ for 6h, and ground through a 200-mesh sieve to obtain modified bentonite 1.

[0046] The product structure was confirmed by infrared spectroscopy, as follows: Figure 1 As shown. Figure 1 As shown, Figure 1 The image shows a comparison of the infrared spectra of sodium-based bentonite, silane-polyether-quaternary ammonium salt modifier, and modified bentonite 1. Sodium-based bentonite exhibits a high infrared spectrum at approximately 3430 cm⁻¹. -1 and 1630cm -1 The OH stretching vibration peak and HOH bending vibration peak of interlayer water / structural hydroxyl groups appear at approximately 1030 cm⁻¹. -1 and 520cm -1 The Si-O-Si stretching vibration peak and the Si-O-Al bending vibration peak appear at approximately 3300 cm⁻¹, which are typical characteristic absorptions of montmorillonite; the silane-polyether-quaternary ammonium salt modifier shows a peak at approximately 3300 cm⁻¹. -1 and 3177cm -1 The stretching vibration of NH occurs at approximately 2920 cm⁻¹. -1 With 2850cm -1 The CH stretching vibration peaks of polyether and alkyl chains appear at approximately 1650 cm⁻¹. -1 and 1550cm -1 A stretching vibration peak of urea / amide groups appears at approximately 1100 cm⁻¹. -1 Strong stretching vibration peaks of the polyether chain COC and Si-O-CH3 were observed at 777 cm⁻¹; -1 The appearance of the Si-O-CH3 bending vibration at approximately 2920 cm⁻¹ confirms the successful synthesis of the silane-polyether-quaternary ammonium salt modifier. Modified bentonite 1 retains the absorption peaks of the sodium-based bentonite framework while exhibiting a peak at approximately 2920 cm⁻¹. -1 With 2850cm -1 A distinct CH stretching vibration peak appears at 1650 cm⁻¹. -1 and 1550cm -1 A stretching vibration peak of urea / amide groups appears at 1100 cm⁻¹, and it is observed at 1100 cm⁻¹. -1The broadening of the characteristic absorption in the vicinity indicates that the modifier has been successfully inserted into the bentonite interlayer and covalently grafted with the hydroxyl groups on the surface and edges of the lamellar layers through hydrolytic condensation of silane groups.

[0047] Modified Bentonite 2: Preparation method is as follows: 100g of sodium-based bentonite was dispersed in deionized water at a solid-liquid ratio of 1:20 and ultrasonically dispersed for 20min to obtain a bentonite suspension. 38.3g of hexadecyltrimethylammonium bromide was weighed according to 1.0 times the CEC of bentonite and dissolved in 200mL of 45℃ deionized water to prepare a clear and transparent quaternary ammonium salt solution. Under stirring, the quaternary ammonium salt solution was slowly added dropwise to the bentonite suspension at a rate of 2-3 drops per second, with the addition time controlled at 30-40min to avoid excessively high local concentrations leading to floc formation. After the addition was complete, the pH of the system was adjusted to 6.5±0.5 with 1mol / L dilute hydrochloric acid or 1mol / L sodium hydroxide solution. The reaction system was heated to 75±2℃ and stirred at a constant temperature for 3h under nitrogen protection. The stirring rate was maintained at 300rpm during the reaction to ensure sufficient ion exchange. After the reaction was completed, the slurry was cooled to room temperature and vacuum filtered. The filter cake was repeatedly washed and filtered with deionized water at 50-60℃, using 500mL of water each time, for a total of 6-8 washes. The final wash filtrate was then treated with 0.1M silver nitrate (AgNO3) solution until no white precipitate or turbidity was observed, indicating complete elution of free bromide ions. The washed filter cake was then placed in a vacuum drying oven and dried at 80℃ and -0.09MPa for 8 hours. The dried lumps were ground in an agate mortar and pestle, passed through a 200-mesh standard sieve (74μm aperture), sealed in a package, and stored away from light to obtain modified bentonite 2.

[0048] Unless otherwise specified, all components and raw materials used in the embodiments and comparative examples of this invention are commercially available, and the same type of components and raw materials are used in each parallel experiment.

[0049] Examples 1-10 A grouting material for filling karst structures, prepared by the following method: S1. Add the thixotropic agent to water accounting for 40% of the total water volume, stir at a high speed of 1500 rpm for 10 minutes to prepare the thixotropic agent mother liquor, and let it stand for 5 minutes to defoam.

[0050] S2. Add ordinary silicate cement, sulfoaluminate cement, fly ash, and silica fume into the mixer and dry mix for 2 minutes.

[0051] S3. Add the remaining 60% water and the thixotropic agent stock solution from S1, and stir at a low speed of 60 rpm for 2 minutes; then add the polycarboxylate superplasticizer solution pre-dissolved in a small amount of water, and stir at a medium speed of 120 rpm for 2 minutes; then add the hydroxypropyl methylcellulose solution pre-dissolved in a small amount of water, and stir for 2 minutes.

[0052] S4. Finally, add the pre-dissolved sodium aluminate and sodium gluconate mixture in a small amount of warm water, stir at 60 rpm for 1 min, and immediately begin grouting. The operating window from the addition of the setting agent to the completion of grouting should be controlled within 30-45 minutes. The specific components and proportions are shown in Table 1.

[0053] Table 1. Components and proportions (parts by weight) of grouting materials in the examples and comparative examples.

[0054] Performance testing 1. Flowability: The flowability test of cement paste was conducted according to GB / T 8077-2023 "Test Method for Homogeneity of Concrete Admixtures". A truncated cone mold (upper inner diameter 36mm, lower inner diameter 60mm, height 60mm, smooth inner wall), a glass plate (400mm×400mm×5mm), and a gyroscope (frequency 1 Hz, amplitude 25mm) were used. Before testing, the inner wall of the truncated cone mold and the glass plate were wiped with a damp cloth until the surface was moist but without standing water. The mold was placed in the center of the glass plate, in two layers. Fill the mold with freshly mixed slurry. Fill the first layer to about 2 / 3 of the height. Use a 10mm diameter stainless steel rod to tamp the slurry evenly from the edge to the center 15 times. Fill the second layer to slightly above the mold opening and tamp it 10 times (each tamping should penetrate the current layer and insert into the next layer). After leveling along the mold opening, gently lift the mold vertically upwards. Start the slurry table to bounce 25 times at a frequency of 1 time / s. After the bouncing is complete, use calipers to measure the diameter of the slurry bottom in two mutually perpendicular directions, accurate to 1mm. Take the average value as the flowability, in mm.

[0055] Note: This method uses a miniature truncated cone mold. If the fluidity of the slurry exceeds the glass plate boundary, a standard truncated cone mold (upper inner diameter 70mm, lower inner diameter 100mm, height 60mm) should be used instead, or the expansion method (500mm frustum) should be used for measurement.

[0056] 2. Marshall funnel viscosity: The viscosity was measured using a standard Marshall funnel viscometer (1500mL funnel volume, conical shape, 4.76mm outlet inner diameter, 50mm outlet length, with a matching 946mL standard measuring cup), a 1.18mm sieve, and a stopwatch with an accuracy of 0.1s. The lower outlet of the funnel was blocked with a finger, and freshly mixed slurry was poured into the funnel through the sieve until the upper surface of the slurry was level with the 1500mL mark. The finger was released and the stopwatch was started at the same time. The time required for the slurry to flow freely and completely fill the 946mL standard measuring cup below was recorded. The test was repeated twice and the arithmetic mean was taken. The difference between the two measurements should not be greater than 3s. Otherwise, the test was repeated. The result was expressed in seconds, and the temperature of the slurry during the test was recorded.

[0057] 3. Bleeding rate: A 100mL graduated glass cylinder (1mL graduation), plastic wrap, and a horizontal settling platform were used for the test. The test method for the bleeding rate of cement paste was referred to in GB / T8077-2023 "Test Method for Homogeneity of Concrete Admixtures". Freshly mixed paste was slowly poured into a 100mL graduated cylinder to the 100mL mark, avoiding the introduction of air bubbles. The top of the graduated cylinder was sealed with plastic wrap to prevent water evaporation. The cylinder was placed on a horizontal settling platform and allowed to stand for 2 hours (for high water-cement ratio or retarded paste, this can be extended to 4 hours or 24 hours until the bleeding stabilizes). The volume of water exuded from the top of the paste, Vw (mL), was then read, accurate to 0.5mL. The bleeding rate was calculated using the formula B=Vw / 100×100%, and the result was expressed as a percentage.

[0058] 4. Setting Time (Initial and Final Setting): Refer to GB / T1346-2011 "Test Methods for Standard Consistency Water Requirement, Setting Time and Soundness of Cement". The setting time is determined using a standard Vicat apparatus (effective needle length 50mm ± 1mm, diameter 1.13mm ± 0.05mm, including initial and final setting needles), a circular mold (upper inner diameter 60mm, lower inner diameter 70mm, height 40mm), and a glass plate (100mm × 100mm × 5mm). The circular mold is placed on the glass plate, and a thin layer of machine oil is applied to the inside. The freshly mixed slurry was poured into a round mold at once, vibrated 5 times or tamped to remove air bubbles, and then leveled. The mold and slurry were then moved into a moisture curing chamber (temperature 20±1℃, relative humidity ≥90%). The time was measured from the moment water was added. Measurements were taken every 5 minutes as the initial setting time approached and every 15 minutes as the final setting time approached. The initial setting time was the time required for the test needle to sink to 4mm±1mm from the bottom plate, and the final setting time was the time required for the test needle to sink to 0.5mm into the surface of the specimen and for the annular attachment to leave no mark on the surface of the specimen. The results were expressed in minutes.

[0059] 5. Thixotropic recovery rate: Measured using a rotational rheometer, a coaxial cylindrical measuring system (rotor diameter 35mm, stator diameter 37mm, gap 1mm, height 30mm), and a constant temperature jacket (temperature control accuracy ±0.1℃). Freshly mixed slurry was loaded into the coaxial cylindrical measuring chamber, the temperature was set to 20±0.5℃, and allowed to stand for 5 minutes to eliminate sample loading history. A low shear rate of 0.1s was then applied. -1 The shear stress T1 (Pa) was recorded at the 30th second after a 30-second interval. The shear rate was then immediately increased to 100 s. -1 The shear stress was maintained for 60 seconds to completely destroy the slurry structure. The shear stress T2 (Pa) at the 60th second was recorded. After stopping the shearing and allowing it to stand for 3 minutes, a low shear rate of 0.1 seconds was applied again. -1 The process lasts for 30 seconds. Record the shear stress T3 (Pa) at the 30th second. Calculate the thixotropic recovery rate using the formula η=(T3-T2) / (T1-T2)×100%. The result is expressed as a percentage. Note: The parameters for the high shear stage should be verified by pre-tests to ensure that the slurry structure has been completely destroyed.

[0060] 6. Dynamic water erosion resistance: The test was conducted using a transparent acrylic water tank (2.00m long, 0.30m wide, 0.30m high), a circulating water pump (adjustable flow rate, equipped with a rotor flow meter, accuracy 0.01m / s), an electronic balance (accuracy 0.1g), and a stainless steel tray (flat bottom, diameter 150mm, height 30mm). Simulated karst groundwater (including 183.0 mg NaHCO3, 71.0 mg Na2SO4, 35.5 mg NaCl, and 61.5 mg MgSO4·7H2O) was injected into the tank. (mg, pH 7.0±0.2), water depth 250mm, weigh 2.00kg of freshly mixed slurry and place it in a stainless steel tray, record the initial mass m0. Fix the tray horizontally at the center of the bottom of the water tank, turn on the water pump and adjust the rotor flow meter to make the water flow velocity reach 0.2m / s. After rinsing for 10min, turn off the water pump, remove the tray, gently absorb the surface free water with filter paper, and weigh the mass m1 of the residue (including partially hardened stone). Calculate the dynamic water erosion resistance rate according to the formula R=m1 / m0×100%, and the result is expressed as %.

[0061] 7. Stone rate: The stone rate was determined using a 100mL graduated glass cylinder (graduation value 1mL) and a standard curing chamber (temperature 20±2℃, relative humidity ≥95%). Freshly mixed slurry was slowly poured into the 100mL graduated cylinder to the 100mL mark, and the initial volume V0 (mL) was recorded. The top of the graduated cylinder was sealed with plastic wrap and placed in the standard curing chamber for 24 hours. After curing, the graduated cylinder was removed, and the cylinder wall was gently tapped to separate the stone from the cylinder wall. The height of the stone was measured, and the actual volume V1 (mL) of the stone was calculated based on the inner diameter of the graduated cylinder, accurate to 1mL. The stone rate was calculated using the formula S=V1 / V0×100%, and the result is expressed as a percentage.

[0062] 8. Compressive strength: The cubic compressive strength test was performed according to JGJ / T70-2009 "Standard for Test Methods of Basic Performance of Building Mortar". A triple mold (70.7mm×70.7mm×70.7mm), a pressure testing machine (accuracy class 1, range 300kN), and a vibration table (frequency 50Hz, amplitude 0.5mm, no-load amplitude 0.35mm) were used for the test. A thin layer of release oil was applied to the inner wall of the mold. Freshly mixed mortar was poured into the mold in one go, placed on the vibration table, and vibrated for 30 seconds. After smoothing the surface, the mold was cured under standard curing conditions (temperature 20±2℃, relative humidity ≥95%) for 28 days. One hour before reaching the test age, the specimens were removed and the surface moisture was wiped off. They were then uniformly loaded at a loading rate of 0.25~1.5kN / s (approximately 0.05~0.3MPa / s) until failure. The failure load F (N) was recorded, and the compressive strength was calculated. The results were expressed in MPa, accurate to 0.1MPa. The arithmetic mean of the three specimens in each group was taken. If the difference between the maximum or minimum value and the median value exceeded 15% of the median value, the median value was taken. If both exceeded 15%, the test results for that group were invalid. For slurries with extremely high fluidity or severe bleeding, a 40mm×40mm×40mm mold could be used to reduce dispersion.

[0063] 9. Permeability Resistance Grade: The permeability resistance test was conducted according to JGJ / T70-2009 "Standard for Test Methods of Basic Performance of Building Mortar". A mortar permeameter (SS-15 type, water pressure range 0.1~1.5MPa) and metal molds (upper diameter 70mm, lower diameter 80mm, height 30mm, truncated cone) were used. Six truncated cone specimens (upper diameter 70mm, lower diameter 80mm, height 30mm) were drilled or cut from the stone body cured for 28 days. The specimens were sealed with paraffin wax on the sides and placed in the permeameter mold (large side down). The permeameter was started, and the water pressure was kept constant at 0.2MPa for 2 hours, then increased to 0.3MPa. Afterward, the water pressure was increased by 0.1MPa every hour. The test was stopped when water seepage appeared on the end faces of three out of the six specimens. The water pressure P (MPa) at this point was recorded. The result was calculated using the formula P... n =10×(P-0.1) to calculate the impermeability grade. The result is represented by P followed by a number (e.g., when P=0.9MPa, the impermeability grade is P8; when P=1.0MPa, the impermeability grade is P9), and so on.

[0064] Table 2 Performance test results of the examples and comparative examples

[0065] The performance test results from the examples and comparative examples show that the grouting material for karst structure filling in Example 1, containing 1.0 wt% modified bentonite 1, exhibits high viscosity at low shear rates. Under these conditions, the detached layers of modified bentonite form a dense three-dimensional network through hydrogen bonding, hydrophobic association, and electrostatic interactions. Under high shear (pumping) conditions, the network breaks down, and the grout thins. After settling, the network rapidly rebuilds, demonstrating excellent thixotropic recovery. This characteristic allows the grout to quickly recover structural strength after injection into a dynamic water environment, resulting in outstanding erosion resistance. Furthermore, the modified bentonite 1 exhibits good compatibility with polycarboxylate superplasticizer, and the combined effect of the dual-cement system and the pozzolanic effect of silica fume contributes to high levels of mechanical properties and impermeability.

[0066] In Example 2, halving the amount of thixotropic agent reduced the node density of the three-dimensional network in the slurry, weakening the structural strength under low shear. Consequently, the thixotropic recovery rate and the resistance to erosion by dynamic water decreased accordingly. However, the reduced interlayer interaction decreased flow resistance, improving the slurry's fluidity and reducing its viscosity. Due to the sparse water-retaining network, free water was more easily released, leading to a slight increase in the bleeding rate. The compressive strength was slightly higher than in Example 1, a difference within the experimental error range, but the trend reflects a slight negative effect of the organic phase of the thixotropic agent on the cement stone structure. Notably, the impermeability grade actually decreased—this is due to the physical barrier of the modified bentonite layers; the reduction in thixotropic agent led to a decrease in the density of the layered network and an increase in the connectivity of micropores. Although the strength increased slightly due to the reduction in the organic phase, the impermeability still showed a slight decrease.

[0067] In Example 3, the addition of thixotropic agent made the three-dimensional network more compact, further improving the thixotropic recovery rate and the resistance to erosion by flowing water. Simultaneously, the increased water content improved the lubricity of the slurry, while maintaining excellent flowability and injectability. The bleeding rate was further reduced due to the enhanced water-retaining network, but the stone formation rate still decreased, the compressive strength decreased, and the impermeability grade also decreased accordingly. These results indicate that there is a water-cement ratio trade-off between thixotropy and mechanical strength; while excessive thixotropic agent improves erosion resistance, it comes at the cost of strength.

[0068] Comparative Example 1 uses unmodified sodium-based bentonite, which relies solely on interlayer Na... + Due to the hydration and expansion effect, and lacking polyether dispersion chains and silane anchoring groups, the lamellae are prone to surface-to-surface aggregation (flocculation) in the high ionic strength environment of cement slurry. The flocs encapsulate a large amount of free water, causing a pseudo-thickness phenomenon: the slurry exhibits extremely high viscosity but poor effective dispersion and very low fluidity. When the floc structure breaks down, the encapsulated water is released, leading to a significant increase in bleeding rate. The floc-formed network is fragile and uneven, difficult to recover after shearing, and exhibits low thixotropic recovery rate and dynamic water erosion resistance. After hardening, the aggregated bentonite introduces local defects and interconnected pores, resulting in poor compressive strength, impermeability, and stone formation rate.

[0069] Comparative Example 2 incorporated conventional CTAB-modified bentonite, in which hexadecyltrimethylammonium bromide (CTAB) enters the interlayer via ion exchange, imparting hydrophobicity to the bentonite and improving interlayer swelling to some extent. However, CTAB is only a single-chain alkyl quaternary ammonium salt, and the dispersion of its lamellar layers in cement slurry is limited, making it difficult to form a uniform three-dimensional network. Therefore, its thixotropic recovery rate and dynamic water erosion resistance are between those of unmodified bentonite and modified bentonite 1. The hydrophobic long chains of CTAB have a weaker lubricating effect on cement particles than polyether chains, and its fluidity and viscosity are inferior to those of Example 1. After hardening, the organic phase distribution is uneven, and the compressive strength and impermeability are at a moderate level.

[0070] Comparative Example 3 replaced modified bentonite with hydroxypropyl methylcellulose and a polycarboxylate superplasticizer. Hydroxypropyl methylcellulose, a linear cellulose ether, thickens and retains water through molecular chain hydration, exhibiting no shear-thinning-recovery properties; therefore, the slurry shows almost no thixotropic behavior. Under dynamic water scouring conditions, the slurry cannot quickly rebuild its structure, exhibiting the lowest scouring resistance among all formulations. Although the strong water-retention effect of hydroxypropyl methylcellulose results in a very low bleeding rate, the thickening mechanism primarily involves encapsulating free water, failing to form an effective lamellar network support. Consequently, the slurry remains viscous but not tough after shearing. Furthermore, the hydroxypropyl methylcellulose molecular chains are linked by hydrogen bonds and Ca... 2+ Complexation adsorbs onto the surface of cement particles, forming a thick hydration adsorption layer, which delays C3S hydration and CSH crystal growth, resulting in unsatisfactory compressive strength and impermeability.

[0071] Comparative Example 4 did not contain sodium gluconate. Sodium gluconate, acting as a retarder, reacts with the Ca released during cement hydration. 2+ The formation of complexes delays CSH nucleation. After removal, the setting-promoting effect of sodium aluminate becomes dominant, significantly accelerating hydration, drastically shortening the setting time, and resulting in a short operating window, which is unfavorable for on-site grouting. However, because modified bentonite 1 is still intact, the thixotropic network of the slurry is not damaged, and the thixotropic recovery rate and dynamic water erosion resistance are close to those of Example 1. The compressive strength is slightly higher than that of Example 1. This is because the absence of the retarder leads to the early formation of a large amount of ettringite in sulfoaluminate cement and inhibits the later crystal transformation (conversion to monosulfo-type hydrated calcium sulfoaluminate), resulting in a more stable crystal structure; at the same time, the hydration process of silicate cement is accelerated, and the two work synergistically to slightly improve the 28-day strength. The impermeability grade remains at a high level. This comparative example demonstrates the necessity of the retarder for the operating window and the independent action mechanism of the thixotropic agent and the retarder.

[0072] Comparative Example 5, without the addition of polycarboxylate superplasticizer, resulted in cement particles losing their electrostatic repulsion and steric hindrance dispersion effects, forming a flocculated structure under the wetting action of water. To achieve pourable fluidity, the water content had to be increased to 65 parts, but the flocculated structure still led to poor pourability. A large amount of free water filled the spaces between the flocs, and after hardening and evaporation, it left behind numerous interconnected pores, significantly increasing the bleeding rate, drastically reducing the stone formation rate, resulting in the lowest compressive strength among all formulations, and extremely poor impermeability. The decrease in thixotropic recovery rate and dynamic water erosion resistance stemmed from the loose structure of the slurry itself, rather than the failure of the thixotropic network. This comparative example demonstrates the synergistic necessity of PCE water-reducing agent and modified bentonite 1: PCE breaks up the flocculation and agglomeration of cement particles, making the distribution of solid particles (cement + bentonite lamellae) in the slurry more uniform, and avoiding the aggregation or failure of modified bentonite lamellae in the gaps between local flocs; at the same time, the polyether side chain of PCE and the PEG chain on the surface of modified bentonite have good compatibility, and the two are synergistically dispersed and neither can be dispensed with.

[0073] The preferred embodiments of the present invention disclosed above are merely illustrative of the invention. These preferred embodiments do not exhaustively describe all details, nor do they limit the invention to the specific implementations described. Clearly, many modifications and variations can be made based on the content of this specification. This specification selects and specifically describes these embodiments to better explain the principles and practical applications of the invention, thereby enabling those skilled in the art to better understand and utilize the invention. The invention is limited only by the claims and their full scope and equivalents.

Claims

1. A grouting material for filling karst structures, characterized in that, The composition, by weight, includes: 50-60 parts of ordinary silicate cement; 15-25 parts of sulfoaluminate cement; 10-20 parts of fly ash; 3-8 parts of silica fume; 0.5-2 parts of thixotropic agent; 1.0-1.5 parts of polycarboxylate superplasticizer; 0.1-0.3 parts of hydroxypropyl methylcellulose; 0.5-1.0 parts of sodium aluminate; 0.03-0.08 parts of sodium gluconate; and 50-60 parts of water. The thixotropic agent is a modified bentonite obtained by organic intercalation and surface covalent grafting modification of sodium-based bentonite using a silane-polyether-quaternary ammonium salt modifier.

2. The grouting material according to claim 1, characterized in that, The silane-polyether-quaternary ammonium salt modifier is prepared by the following steps: (1) reacting a polyamine with an isocyanate-based silane to obtain a urea polyamine containing a silane group; (2) reacting the urea polyamine containing a silane group with a polyether carboxylic acid active ester to obtain a polyether-amide-urea-silane intermediate; (3) subjecting the polyether-amide-urea-silane intermediate to a haloalkane alkylation and quaternization reaction with a quaternizing agent to obtain the silane-polyether-quaternary ammonium salt modifier.

3. The grouting material according to claim 2, characterized in that, The polyamine is diethylenetriamine, the isocyanate-based silane is 3-isocyanate-based propyltrimethoxysilane, and the molar ratio of the polyamine to the isocyanate-based silane is (5~15):

1.

4. The grouting material according to claim 2, characterized in that, The polyether carboxylic acid is methoxy polyethylene glycol-carboxylic acid with an average molecular weight of 500-600; in step (3), the haloalkane is a bromoalkane with 6-12 carbon atoms, and the quaternizing agent is iodomethane or dimethyl sulfate.

5. The grouting material according to claim 1, characterized in that, The modified bentonite is prepared through the following steps: (1) Disperse sodium-based bentonite in water, add silane-polyether-quaternary ammonium salt modifier to carry out intercalation reaction, and obtain intercalated bentonite; (2) The intercalated bentonite is subjected to a hydrothermal reaction under alkaline conditions, so that the silane groups in the modifier are hydrolyzed and condensed with the hydroxyl groups on the surface and edge of the bentonite sheets to obtain modified bentonite.

6. The grouting material according to claim 5, characterized in that, In step (1), sodium-based bentonite is dispersed in deionized water at a solid-liquid ratio of 1:(15~25), and the amount of silane-polyether-quaternary ammonium salt modifier added is 2wt%~5wt% of the bentonite mass. The reaction temperature is 30~45℃ and the reaction time is 1~3h. In step (2), the pH is adjusted to 9~11, the reaction temperature is 50~70℃, and the reaction time is 2~4h. The cation exchange capacity of the sodium-based bentonite is 95~110mmol / 100g, and the montmorillonite content is ≥75%.

7. The method for preparing karst structure filling grouting material according to any one of claims 1 to 6, characterized in that, Includes the following steps: S1. Disperse the thixotropic agent in a portion of water to prepare a thixotropic agent stock solution; S2. Dry mix ordinary Portland cement, sulfoaluminate cement, fly ash, and silica fume evenly; S3. Add the remaining water and the thixotropic agent mother liquor described in S1, and stir to obtain a slurry; then add the polycarboxylate superplasticizer solution and hydroxypropyl methylcellulose solution, and continue stirring; S4. Finally, add the mixed solution of sodium aluminate and sodium gluconate, stir evenly, and immediately carry out the grouting operation.

8. The preparation method according to claim 7, characterized in that, In step S1, the modified bentonite is added to water accounting for 30% to 50% of the total water volume, and stirred at a high speed of 1000 to 2000 rpm for 5 to 15 minutes, followed by standing to defoam; in step S2, the dry mixing time is 1 to 3 minutes; in step S3, the mixture is first stirred at a low speed for 1 to 3 minutes, and then the polycarboxylate superplasticizer solution and hydroxypropyl methylcellulose solution are added and stirred at a medium speed for 1 to 3 minutes; in step S4, the mixture is stirred at a low speed for 0.5 to 2 minutes; from the addition of the setting agent to the completion of grouting, the operating window is controlled within 30 to 45 minutes.

9. A silane-polyether-quaternary ammonium salt modifier, characterized in that, The silane-polyether-quaternary ammonium salt modifier is prepared by the following steps: (1) reacting a polyamine with an isocyanate-based silane to obtain a urea polyamine containing a silane group; (2) reacting the urea polyamine containing a silane group with a polyether carboxylic acid active ester to obtain a polyether-amide-urea-silane intermediate; (3) subjecting the polyether-amide-urea-silane intermediate to a haloalkane alkylation and quaternization reaction with a quaternizing agent to obtain the silane-polyether-quaternary ammonium salt modifier.

10. A modified bentonite, characterized in that, The modified bentonite is prepared through the following steps: (1) Disperse sodium-based bentonite in water, add silane-polyether-quaternary ammonium salt modifier to carry out intercalation reaction, and obtain intercalated bentonite; (2) The intercalated bentonite is subjected to a hydrothermal reaction under alkaline conditions, so that the silane groups in the modifier are hydrolyzed and condensed with the hydroxyl groups on the surface and edge of the bentonite sheets to obtain modified bentonite.

Citation Information

Patent Citations

  • Grouting material suitable for filling karst caves or earth caves in karst area as well as grouting and filling construction method

    CN108585692A